The Promise of Promise: Retrospect and Prospect of a Homiletical Theology (Homiletic, 2013)
North American homiletical theology has been increasingly retrieving and revising a theology of promise for preaching. This article offers a Forschungsbericht concerning the use of promise in homiletical theology. It does so initially by retracing traditions of promise with respect to multiple theological concerns: the dialectic of promise and law in the gospel, the role of promise in eschatology, Word and Sacrament, and in theologies of the scriptures with respect to Old and New Testaments. The essay next considers the place of promise in contemporary homiletics. It discusses treatments of promise in the work of North American homileticians James Kay, Dawn Ottoni Wilhelm, David Lose, Olin Moyd, Christine Smith, David Schnasa Jacobsen, Richard Lischer, and Paul Wilson as well as briefly treating promise in light of the broader concerns of Eunjoo Mary Kim, Kenyatta Gilbert, Dale Andrews, and Ronald Allen and Joey Jeter. The article suggests future promising areas of research and lays a groundwork for future scholarly contributions.